Detection of Bacterial Virulence Genes by Subtractive Hybridization: Identification of Capsular Polysaccharide of Burkholderia pseudomallei as a Major Virulence Determinant - Reckseidler, Shauna L. (American Society for Microbiology, 2001)
Burkholderia pseudomallei, the etiologic agent of melioidosis, is responsible for a broad spectrum of illnesses in humans and animals particularly in Southeast Asia and northern Australia, where it is endemic. Burkholderia thailandensis is a nonpathogenic environmental organism closely related to B. pseudomallei. Subtractive hybridization was carried out between these two species to identify genes encoding virulence determinants in B. pseudomallei. Screening of the subtraction library revealed A-T-rich DNA sequences unique to B. pseudomallei, suggesting they may have been acquired by horizontal transfer. One of the subtraction clones, pDD1015, encoded a protein with homology to a glycosyltransferase from Pseudomonas aeruginosa. This gene was insertionally inactivated in wild-type B. pseudomallei to create SR1015. It was determined by enzyme-linked immunosorbent assay and immunoelectron microscopy that the inactivated gene was involved in the production of a major surface polysaccharide. The 50% lethal dose (LD(50)) for wild-type B. pseudomallei is <10 CFU; the LD(50) for SR1015 was determined to be 3.5 × 10(5) CFU, similar to that of B. thailandensis (6.8 × 10(5) CFU). DNA sequencing of the region flanking the glycosyltransferase gene revealed open reading frames similar to capsular polysaccharide genes in Haemophilus influenzae, Escherichia coli, and Neisseria meningitidis. In addition, DNA from Burkholderia mallei and Burkholderia stabilis hybridized to a glycosyltransferase fragment probe, and a capsular structure was identified on the surface of B. stabilis via immunoelectron microscopy. Thus, the combination of PCR-based subtractive hybridization, insertional inactivation, and animal virulence studies has facilitated the identification of an important virulence determinant in B. pseudomallei.